2003
DOI: 10.1016/s0378-1097(03)00839-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of free and organic iodine byRoseovariusspp.

Abstract: Two strains of iodine-producing bacteria were isolated from marine samples. 16S rRNA gene sequences indicated the strains were most closely related to Roseovarius tolerans, and phylogenetic analysis indicated both belong to the same genus. 5 mM iodide inhibited the growth of strain 2S5-2 almost completely, and of strain S6V slightly. Both strains produced free iodine and organic iodine from iodide. CH 2 I 2 , CHI 3 and CH 2 ClI were the main organic iodines produced by strain 2S5-2, and CHI 3 and CH 2 I 2 by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 34 publications
0
57
0
Order By: Relevance
“…CH 3 I and CH 2 I 2 has been observed in the field and the laboratory (Manley and Dastoor, 1988;Amachi et al, 2001;Fuse et al, 2003;Amachi, 2008). Large uncertainties regarding the production of halocarbons in the ocean remain.…”
Section: H Hepach Et Al: Halocarbons In the Atlantic Cold Tonguementioning
confidence: 98%
See 1 more Smart Citation
“…CH 3 I and CH 2 I 2 has been observed in the field and the laboratory (Manley and Dastoor, 1988;Amachi et al, 2001;Fuse et al, 2003;Amachi, 2008). Large uncertainties regarding the production of halocarbons in the ocean remain.…”
Section: H Hepach Et Al: Halocarbons In the Atlantic Cold Tonguementioning
confidence: 98%
“…4, 5) could indicate similar production and sink processes at depth. Bacterial formation of CH 2 I 2 (Fuse et al, 2003;Amachi et al, 2005) in the upper thermocline could also be an additional source for this compound. Alternatively, CH 2 I 2 may not degrade as quickly as CHBr 3 and CH 3 I in greater depths, which would lead to its accumulation below the mixed layer.…”
Section: Ch 3 I and Ch 2 Imentioning
confidence: 99%
“…The concentrations are a result of production and loss processes, which may partly be temporally and spatially decoupled. Another possible source for CH 3 I involves bacteria (Manley and Dastoor, 1998;Amachi et al, 2001;Fuse et al, 2003) which has not been taken into account during DRIVE. Additionally, Bell et al (2002) suggested that organic precursors from phytoplankton production could be involved in the photochemical formation of CH 3 I in the surface ocean.…”
Section: Oceanic and Atmospheric Ch 3 I As Drivers Of The Regional Anmentioning
confidence: 99%
“…(α-Proteobacteria), one isolated from marine sediment and another from seawater (Fuse et al, 2003). Organic iodine species, including CH 3 I, CH 2 ClI, CH 2 I 2 , and CHI 3 , were also produced from iodide by these strains, and it was suggested that organic acids in the media or produced by the strains could be the carbon sources for these organo-iodine products.…”
Section: Microbiological Oxidation Of Iodinementioning
confidence: 99%